Beach Cleaning Action Movement as an Effort to Create Environmentally Friendly Tourism on Kapu Beach, Kolaka Regency - Nurfadillah; Ardiansyah, Awi; Astuti, Dwi; Mutmainna, Mutmainna; Nurhalizah, Nurhalizah; Saputra, Fahmi; Ahyar, Haeril; Syaiful, Muhammad; Anggraini, Yuyun (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2024)
Kolaka is one of the districts in Southeast Sulawesi. Kolaka Regency is a coastal area located in Southeast Sulawesi Province. Kolaka is like a hidden paradise on the west coast of Sulawesi Island. As a large area that borders the sea, namely Bone Bay to the west. Kolaka Regency has a coastline that stretches for 293.45 km, decorated with white sandy beaches, clear sea water. One potential that is worth paying attention to as a tourist destination is Kapu Beach, which is located in Kapu Village, Samaturu District, Kolaka Regency. However, currently, Kapu Beach is polluted with lots of plastic and organic waste scattered around and reducing the beauty of the beach. The method used in this activity is the observation method. The first stage that was carried out began with coordination with the local government and the management of Kapu Beach. The second stage, namely checking the condition of the tourist beaches that would be cleaned, as well as preparing paint for re-tightening the trees and aesthetic photo spots. The third stage, This stage carries out the process of cleaning the beach tourism environment and painting several photo spots. What is meant by the observation method is a way of collecting information from relevant data by observing. The result of this activity for the surrounding community is to build self-awareness for the community to care about the beach and coastal environment and also be aware of the dangers of environmental pollution, considering that the location where they live is on the coast of Kapu Village. Based on the results of the service carried out, the conclusion that can be drawn from the beach clean-up activity is that it was held smoothly and in accordance with the previously planned activity structure, and cleaning up rubbish at the tourist attraction was not easy, the large number of visitors not only had a positive impact on tourist attractions but there There is also a negative impact, namely, where a lot of plastic waste is found both around the gazebo and even on the coast, there is also a lot of waste used from visitors' food. It is important to maintain the cleanliness of the beach tourism environment so that it can be managed well and optimally.